Bleeding-edge entrepreneurship : digitalization, blockchains, space, the ocean, and artificial intelligence - Ferreira, João J.; Murphy, Patrick J. (Contemporary issues in entrepreneurship research ;, 2023)
This book contains an Open Access chapter The continued rise of the digital age and its radical innovation activities compel us to reconceptualize how entrepreneurial ventures and other organizations use various technologies to grow, evolve, and perform. How do the boldest entrepreneurship theories assist in this reconceptualization? Entrepreneurship has been heralded for decades as a revolutionary movement within the domain of business theory and practice. If so, then what are the most powerful and significant aspects of this entrepreneurial revolution? Bleeding-edge Entrepreneurship illuminates new possibilities, expanding entrepreneurship's massive potential to create unexplored physical and virtual realms. The contributors are worldwide experts in technology-enabled entrepreneurship and social enterprise. The chapters cover a wide range of entrepreneurial phenomena, theories, and practices. Delineating the very best practices for venture performance in the world's most progressive realms, illustrating the nature of impact in extreme uncertainty, and shaping public policy regarding all these activities, Bleeding-edge Entrepreneurship is required reading for practitioners and academics in all fields of business, but especially those who are interested in entrepreneurship. Contemporary Issues in Entrepreneurship Research is an official book series of the Institute for Small Business and Entrepreneurship (ISBE). Each volume is designed around a specific theme of importance to the entrepreneurship and small business community with articles collectively exploring and developing theory and practice in the field.